Теоретическая и эмпирическая интерпретация и операционализация понятия “валидность” - Никитина, Т. (Iнститут соціології НАН України, 2009)
Validity is one of the basic properties of empirical measurement. A common definition of validity is the extent to which the survey measure accurately reflects the intended construct. But in different sociological source of information there are different understandings of the domain of validity. Some researchers understand validity as a property of measurement, while others - as a property of measurement instrument. Researchers determine different types of validity. There is no standardization of notions. Such situation complicates the process of validation of particular measurement. In fact, there is no concrete pattern of measurements validation. The purpose of this article is to make theoretical and empirical interpretation and operationalization of the validity notion and as a result develop the concrete pattern of measurements validation.